Inovasi Olahan Biji Alpukat Menjadi Teh Sebagai peluang Peningkatan Ekonomi di Desa Wisata Sembalun - Payumi, Erika Triya; Ayuliana, Ravita Nur; Nurmayani, Yunita; Erlani; Mahyuni, Ani; Lestari, Nuya; Pratama, Dimas Arya; Putra, Hardiyan Maolana; Darmawan, Ida Bagus Satya; Pratama, Fendy Adyatma (Universitas Mataram, 2025)
Avocados are classified as fruits that are rich in vitamins A, B, C, E and contain the elements potassium and carotene. The highest potassium content is found in the avocado seed, which functions to eliminate excess toxins in the body. Generally, people only consume the flesh of the fruit and throw away the seeds so that avocado seed waste is not processed into economically valuable products or for personal use. This service aims to educate and train the skills of the community in Sembalun Village, East Lombok Regency in creating innovative Avotea Seed products made from avocado seed waste, as well as helping the skills they already have to become entrepreneurial opportunities for the community. The method used is education about the manufacture and use of avocado seeds and direct practice of processing avocado seeds into Avotea Seed products to the people of Sembalun Village, East Lombok Regency. The result of the service that has been carried out is the result of education and training in making tea products from avocado seed waste, showing that the people of Sembalun Village, East Lombok Regency are starting to understand the benefits of avocado seeds.